Towards a better estimation of prevalence of female genital mutilation in the European Union: a situation analysis - L. De Schrijver; L. Van Baelen; N. Van Eekert; E. Leye (BMC, 2020)
Abstract Background Female genital mutilation (FGM) is a harmful cultural practice that is predominantly documented in Africa, but also occurs in other parts of the world. Due to migration, women who have undergone FGM can also be found in the European Union (EU). Due to a lack of systematic representative surveys on the topic in EU, the prevalence of FGM and the number of women and children subjected to the practice remains unknown. However, information on the magnitude of the problem in the EU is necessary for policy makers to design and track preventive measures and to determine resource allocation. Methods Between March 2015 and May 2015, we performed a situation analysis consisting of a critical interpretive synthesis and SWOT-analysis of available at the time peer reviewed and grey literature document on national prevalence studies on FGM in the EU. Studies estimating the prevalence of FGM and the number of girls and women subjected to the practice in the EU were mapped to analyse their methodologies and identify their Strengths, Weakness, Opportunities and Threats (SWOT). Distinction was made between direct and indirect estimation methods. Results Thirteen publications matched the prioritized inclusion criteria. The situation analysis showed that both direct and indirect methodologies were used to estimate FGM prevalence and the number of girls and women subjected to FGM in the EU. The SWOT-analysis indicated that due to the large variations in the targeted population and the available secondary information in EU Member States, one single estimation method is not applicable in all Member States. Conclusions We suggest a twofold method for estimating the number of girls and women who have undergone fgm in the EU. For countries with a low expected prevalence of women who have undergone fgm, the indirect method will provide a good enough estimation of the FGM prevalence. The extrapolation-of-fgm-countries-prevalence-data-method, based on the documented FGM prevalence numbers in DHS and MICS surveys, can be used for indirect estimations of girls and women subjected to FGM in the eu. For countries with a high expected prevalence of FGM in the EU Member State, we recommend to combine both a direct estimation method (e.g. in the form of a survey conducted in the target population) and an indirect estimation method and to use a sample design as developed by the FGM-PREV project. The choice for a direct or indirect method will ultimately depend on available financial means and the purpose for the estimation.